Students’ Learning Motivation through the Quality of Scientific Argumentation Skills and Students’ Cognitive Learning Outcomes on Newton's Laws: A Relationship Analysis - Betari, Almira; Hasanati, Alvi; Fuadah, Fitroh; Amir, Muhammad Taufiqurrahman; Parno, Parno (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
Theory about Newton's Law is considered difficult for students. Many students cannot solve Newton's Law’s problems caused they cannot understand the concept. Concept understanding requires complex learning by increasing students’ motivation. This study aimed to explore the relationship between students’ motivation through scientific argumentation skills and students’ learning outcomes on Newton's laws. This research was a non-experimental mixed-method study with an embedded-correlational research design. The subjects of this study were 32 students of Senior High School (SMA) Laboratory UM Malang (State University of Malang). The sampling technique used in the study was purposive sampling, specifically homogeneity sampling. The research instrument consisted of open-ended questions, semi-structured interviews, questionnaires, and document identification. The data analysis technique used was a partial correlation test for quantitative data and descriptive analysis through coding for qualitative data. The results showed that the quality of students' scientific arguments was most dominant at Level 2. The arguments consisted of claims supported by data. However, the students sometimes claimed incorrect understanding of Newton's Laws I and II. The results of the partial correlation test between motivation and scientific argumentation and student cognitive learning outcomes did not show any correlation. However, there was a positive effect.